2016
DOI: 10.5194/aab-59-183-2016
|View full text |Cite
|
Sign up to set email alerts
|

Improving the fatty acid profile in egg yolk through the use of hempseed (<i>Cannabis sativa</i>), ginger (<i>Zingiber officinale</i>), and turmeric (<i>Curcuma longa</i>) in the diet of Hy-Line White Leghorns

Abstract: Abstract.A study was performed to examine the outcome of utilizing hempseed, ginger, and turmeric in the diet of Hy-Line White Leghorn on the fatty acid profile of egg yolk. Four experimental rations were offered to 60 laying hens: control (standard diet); 25 % hempseed (T1); 25 % hempseed and 2 % turmeric (T2); 25 % hempseed and 2 % ginger (T3). Thirty eggs per group were analysed on day 0, 15, and 30 after storage at room temperature. Individual and total fatty acids decreased significantly (P < 0.05) in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
23
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 34 publications
5
23
0
1
Order By: Relevance
“…The inclusion of hemp seed or hempseed cake dramatically reduced the LA : ALA ratio in egg yolks from 27.8 : 1 in the control diet to 4.6 -6.4 : 1 in the HS and HC diets (see Table 4). This is due to the high amount of ALA in hemp seed and hempseed cake, consistent with the findings of previous studies which showed a reduced LA : ALA ratio in eggs from hens consuming diets containing hemp seed (Gakhar et al, 2012;Raza et al, 2016) or hempseed oil (Neijat et al, 2016).…”
Section: Resultssupporting
confidence: 92%
“…The inclusion of hemp seed or hempseed cake dramatically reduced the LA : ALA ratio in egg yolks from 27.8 : 1 in the control diet to 4.6 -6.4 : 1 in the HS and HC diets (see Table 4). This is due to the high amount of ALA in hemp seed and hempseed cake, consistent with the findings of previous studies which showed a reduced LA : ALA ratio in eggs from hens consuming diets containing hemp seed (Gakhar et al, 2012;Raza et al, 2016) or hempseed oil (Neijat et al, 2016).…”
Section: Resultssupporting
confidence: 92%
“…The higher feed intake was also recorded in ginger and garlic supplemented groups, while the lowest feed intake was recorded in the positive control. Ginger contains several important pharmacological compounds such as gingerdione, gingerdiol, shogaols and gingerol (Raza et al 2016). The improved performance in broiler fed with ginger has been linked with the enhanced palatability and improved digestive process which increase the feed intake and hence weight gain (Khan et al 2012a).…”
Section: Discussionmentioning
confidence: 99%
“…Garlic (Allium sativum) contains important alkaloids such as allin, ajoene, allicin and diallyl sulphide Sallylcysteine exhibiting antibacterial, anti-inflammatory, antiseptic, antiparasitic and immunomodulatory properties (Adibmoradi et al 2006;Khan et al 2012a). Ginger (Zingiber officinale) contains active ingredients such are gingerdoine, gengerdiol and gingerol (Khan et al 2012b; Raza et al 2016;Zia ur Rehman et al 2018). Ginger has been reported to enhance the growth performance and digestibility in broilers and effective in treating and controlling coccidial infection (Zhang et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Active constituents in the herbal plants are discovered as a source of antioxidants (Khan et al 2012b;Raza et al 2016). Ginger (Zingiber officinale) is best and commonly used spices.…”
Section: Introductionmentioning
confidence: 99%